Music and social justice : a guide for elementary educators - Benedict, Cathy, 4 0 16; 5 (New York : Oxford University Press, 2021)
In this book Cathy Benedict challenges and reframes traditional ways of addressing many of the topics we have come to think of as social justice. Offering practical suggestions for helping both teachers and students think philosophically (and thus critically) about the world around them, each chapter engages with important themes through music making and learning as it presents scenarios, examples of dialogue with students, unit ideas and lesson plans geared toward elementary students (ages 6-14). Taken-for-granted subjects often considered sacrosanct or beyond the understanding of elementary students such as friendship, racism, poverty, religion, and class are addressed and interrogated in such a way that honours the voice and critical thinking of the elementary student--
Listening and Responding : Dialogue in Practice -- Communicating Justice and Equity : Meeting the Other -- Friendship and Bullying : Interrogating Forced Narratives -- Soundscapes : Listening for Meaningful Relationships - In Conversation with Kelly Bylica -- Educating for Intelligent Belief or Unbelief -- Politics of Song -- Policy and Teaching : Establishing Change - In Conversation with Patrick Schmidt.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Instruction and study;Social aspects. -- Music;Social justice and education.;Education, Elementary. -- 20; 20; 2